IDNLearn.com offers a collaborative platform for sharing and gaining knowledge. Get timely and accurate answers to your questions from our dedicated community of experts who are here to help you.

1. Simplify the following expressions:

a) [tex]\((3x + 4)^2 =\)[/tex]

b) [tex]\((2x + 4)(2x - 6) =\)[/tex]


Sagot :

Certainly! Let's go through each part step-by-step.

### Part a: Expand [tex]\((3x + 4)^2\)[/tex]

To expand [tex]\((3x + 4)^2\)[/tex], you can use the formula for the square of a binomial: [tex]\((a + b)^2 = a^2 + 2ab + b^2\)[/tex].

In this case, [tex]\(a = 3x\)[/tex] and [tex]\(b = 4\)[/tex].

So, we have:
[tex]\[ (3x + 4)^2 = (3x)^2 + 2 \cdot (3x) \cdot 4 + 4^2 \][/tex]

Now, calculate each term:
- [tex]\((3x)^2 = 9x^2\)[/tex]

- [tex]\(2 \cdot (3x) \cdot 4 = 2 \cdot 3 \cdot 4 \cdot x = 24x\)[/tex]

- [tex]\(4^2 = 16\)[/tex]

Putting it all together:
[tex]\[ (3x + 4)^2 = 9x^2 + 24x + 16 \][/tex]

### Part b: Expand [tex]\((2x + 4)(2x - 6)\)[/tex]

To expand [tex]\((2x + 4)(2x - 6)\)[/tex], you can use the distributive property (also known as the FOIL method for binomials).

[tex]\[ (2x + 4)(2x - 6) = 2x(2x) + 2x(-6) + 4(2x) + 4(-6) \][/tex]

Now, calculate each term:
- [tex]\(2x \cdot 2x = 4x^2\)[/tex]

- [tex]\(2x \cdot (-6) = -12x\)[/tex]

- [tex]\(4 \cdot 2x = 8x\)[/tex]

- [tex]\(4 \cdot (-6) = -24\)[/tex]

Now, combine like terms:
[tex]\[ (2x + 4)(2x - 6) = 4x^2 - 12x + 8x - 24 \][/tex]

Combining [tex]\(-12x\)[/tex] and [tex]\(8x\)[/tex]:
[tex]\[ 4x^2 - 12x + 8x - 24 = 4x^2 - 4x - 24 \][/tex]

### Final Answer:

a) [tex]\((3x + 4)^2 = 9x^2 + 24x + 16\)[/tex]

b) [tex]\((2x + 4)(2x - 6) = 4x^2 - 4x - 24\)[/tex]